Study and influence of clove, cinnamon, and orange essential oils in the preparation of poly (lactic acid) films: Active packaging development (Research, Society and Development, 2021)
Poly (lactic acid) - PLA is a biocompatible and biodegradable polymer with some properties similar to conventional polymers, standing out in several applications, among them, the packaging industry. The substitution of conventional additives for natural components such as essential oils, has become a promising alternative for the production of so-called active packaging, which promote food safety from the antimicrobial action. Therefore, the objective of this work was to produce PLA films by casting with essential oils (OE) of cloves, orange and cinnamon, for its possible application as an active packaging. The oils were characterized by Gas Chromatography coupled with Mass Spectrometer (GC-MS), Fourier transform infrared spectroscopy (FTIR) and by agar disc diffusion. The films were characterized by Optical Microscopy (MO), Differential Scanning Calorimetry (DSC), FTIR, Thermogravimetric Analysis (TG) and Antimicrobial Analysis of the film. With the results obtained it was possible to observe that the PLA film with essential oils showed an improvement in performance regarding its thermal property and antimicrobial activity. Among the three additive films, the PLA / OE Cravo film stood out for having an intense bactericidal action without degradation of the film, which makes it a promising additive added to PLA for applications in packaging industries.